MEDIASI SOSIAL DALAM MENYELESAIKAN KONFLIK LAHAN MILIK MASYARAKAT ADAT DI INDONESIA (Lex Jurnalica, 2017)
AbstractThe emergence of conflicts lands of indigenous peoples in Indonesia due to the lack of government attention to the existence of indigenous peoples. All lands occupied by indigenous communities had many converted to the production of land belonging to the corporation. This gives rise to jealousy and a sense of injustice within the indigenous peoples as a result of the land is minimal perceived by the people around. As a result of social conflict arises. To handle social conflicts that need to be empowered and the role of traditional leaders as a social mediator. The participation of traditional leaders is very important because indigenous people are more likely to hear and obey the words and decisions of traditional leaders.Keywords: social conflict, indigenous lands, social mediation Â AbstrakMunculnya konflik lahan milik masyarakat adat di Indonesia disebabkan kurangnya perhatian pemerintah terhadap keberadaan masyarakat adat. Lahan-lahan yang semua dikuasai oleh komunitas adat telah banyak yang beralih fungsi menjadi lahan-lahan produksi milik korporasi. Hal ini menimbulkan kecemburuan dan rasa ketidakadilan didalam masyarakat adat karena hasil dari lahan tersebut dirasakan minim oleh masyarakat sekitar. Akibatnya muncul konflik sosial. Untuk menangani konflik sosial maka perlu diberdayakan peran serta tokoh-tokoh adat sebagai mediator sosial. Peran serta tokoh adat sangat penting karena masyarakat adat lebih cenderung mendengar dan mematuhi tutur kata dan keputusan dari tokoh adat.Kata kunci: konflik sosial, lahan adat , mediasi sosial